A new specimen of the theropod dinosaur Baryonyx from the early Cretaceous of Portugal and taxonomic validity of Suchosaurus - Mateus, Octávio; Araújo, Ricardo; Natário, Carlos; Castanhinha, Rui (Zootaxa, 2011)
Although the Late Jurassic of Portugal has provided abundant dinosaur fossils, material from the Early Cretaceous is scarce. This paper reports new cranial and postcranial material of the theropod dinosaur Baryonyx walkeri found in the Barremian (Papo Seco Formation) of Portugal. This specimen, found at Praia das Aguncheiras, Cabo Espichel, consists of a partial dentary, isolated teeth, pedal ungual, two calcanea, presacral and caudal vertebrae, fragmentary pubis, scapula, and rib fragments. It represents the most complete spinosaurid yet discovered in the Iberian Peninsula and the most complete dinosaur from the Early Cretaceous of Portugal. This specimen is confidently identified as a member of Baryonychinae due to the presence of conical teeth with flutes and denticles in a dentary rosette. The specimen ML1190 shares the following characteristics with Baryonyx walkeri: enamel surface with small (nearly vertical) wrinkles, variable denticle size along the carinae, 6–7 denticles per mm, wrinkles forming a 45 degree angle near the carinae, and tooth root longer than crown. In addition, dubious taxa based on teeth morphology such as Suchosaurus cultridens (Owen, 1840–1845), and Suchosaurus girardi (Sauvage 1897–98; Antunes & Mateus 2003) are discussed, based on comparisons with well-known material such as Baryonyx walkeri Charig & Milner, 1986. Suchosaurus cultridens and S. girardi are considered as nomina dubia due to the lack of diagnostic apomorphies, but both specimens are referred to Baryonychinae incertae sedis.